2019
DOI: 10.1037/pspi0000148
|View full text |Cite
|
Sign up to set email alerts
|

Broadening your horizons: Self-expanding activities promote desire and satisfaction in established romantic relationships.

Abstract: In the early stages of romantic relationships, sexual desire is often intense, but over time, as partners get to know each other, desire tends to decline. Low sexual desire has negative implications for relationship satisfaction and maintenance. Self-expansion theory suggests that engaging in novel activities with a long-term romantic partner can reignite feelings of passion from the early stages of a relationship. Across 3 studies using dyadic, daily experience, longitudinal, and experimental methods, we find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
164
3
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(186 citation statements)
references
References 76 publications
14
164
3
5
Order By: Relevance
“…New and exciting couple activities are important to intimate relationships because they help promote increased relationship satisfaction (e.g., Aron & Aron, 1986;1997;Aron, Norman, Aron, McKenna, & Heyman, 2000;Girme, Overall, & Faingataa, 2014;Graham, 2008;Harasymchuk & Fehr, 2010;Mattingly & Lewandowski, 2013;Muise, Harasymchuk, Day, Bacev-Giles, Gere, & Impett, 2019;Reissman, Aron, & Bergen, 1993). However, people's quest for seeking novelty within their relationship may not always be a positive experience because of perceived threats to their relationship.…”
Section: Self-expansionmentioning
confidence: 99%
See 4 more Smart Citations
“…New and exciting couple activities are important to intimate relationships because they help promote increased relationship satisfaction (e.g., Aron & Aron, 1986;1997;Aron, Norman, Aron, McKenna, & Heyman, 2000;Girme, Overall, & Faingataa, 2014;Graham, 2008;Harasymchuk & Fehr, 2010;Mattingly & Lewandowski, 2013;Muise, Harasymchuk, Day, Bacev-Giles, Gere, & Impett, 2019;Reissman, Aron, & Bergen, 1993). However, people's quest for seeking novelty within their relationship may not always be a positive experience because of perceived threats to their relationship.…”
Section: Self-expansionmentioning
confidence: 99%
“…By nature, the self-expansion process is positive and rewarding for intimate relationships. Research has found that people who experience greater levels of relational self-expansion tend to reap rewards such as greater relationship quality (e.g., Aron et al, 2000;Carson, Carson, Gil, & Baucom, 2004;Coulter & Malouff, 2013;Muise et al, 2019;Reissman et al, 1993), and greater individual well-being (Aron et al, 2004;Mattingly & Lewandowski, 2013). For instance, through two 21-day daily diary studies of couples, Muise and colleagues (2019) assessed relational self-expansion through a daily selfreport measure and found that people reported greater relationship satisfaction as well as increased sexual desire on days when their evaluations of relational self-expansion were greater than usual.…”
Section: Self-expansion Modelmentioning
confidence: 99%
See 3 more Smart Citations